Genetic and environmental variance components for physical activity patterns of twins. Exploring the possibilities of approximate entropy - José António Ribeiro Maia; André Seabra; Rui Garganta; Rogério César Fermino; Ramon de Brito Costa Pinheiro Lima (Universidade Federal de Santa Catarina, 2010)
The main objective of this study was to estimate the contribution of genetic factorsto physical activity patterns (PAPs) in twins using approximate entropy (ApEn) statistics. Thesample consisted of 162 monozygotic and dizygotic twins from Portugal aged 6 to 18 years.Physical activity was measured with a Tritrac-RT3 triaxial accelerometer over 5 days of a usualweek. PAPs were described by ApEn using the Cine Wizard software. Zygosity was assessed bydirect DNA analysis. Data were analyzed using the SYSTAT 10, STATA 10 and Twinan92softwares. PAPs were estimated for 5, 3 and 2 days. In addition, structural equation modelingwas used to compute different sources of variance genetic, common environmental and uniqueenvironmental variance.The level of significance was set at 5%. Sibling aggregation was identifiedby ApEn analysis, with monozygotic twins showing greater homogeneity. In conclusion, geneticfactors accounted for 44 to 89% of the total variation in PAP.